2014
DOI: 10.1016/j.smim.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Orchestration of pulmonary T cell immunity during Mycobacterium tuberculosis infection: Immunity interruptus

Abstract: Despite the introduction almost a century ago of Mycobacterium bovis BCG (BCG), an attenuated form of M. bovis that is used as a vaccine against Mycobacterium tuberculosis, tuberculosis remains a global health threat and kills more than 1.5 million people each year. This is mostly because BCG fails to prevent pulmonary disease – the contagious form of tuberculosis. Although there have been significant advances in understanding how the immune system responds to infection, the qualities that define protective im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 245 publications
(293 reference statements)
2
40
1
3
Order By: Relevance
“…However, CD8 + T cells appear to be less effective than CD4 + T cells in mediating resistance, despite similar kinetics (28, 35, 42). There are numerous potential signals that modify T cell responses in a diseased lung – soluble mediators and cell surface signals can have both positive and negative effects on T cell expansion and function (43). While it is commonly accepted that optimal CD8 + T cell responses require a third signal – usually mediated by an inflammatory cytokine – how CD8 + T cells are regulated during chronic inflammation is less well understood (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, CD8 + T cells appear to be less effective than CD4 + T cells in mediating resistance, despite similar kinetics (28, 35, 42). There are numerous potential signals that modify T cell responses in a diseased lung – soluble mediators and cell surface signals can have both positive and negative effects on T cell expansion and function (43). While it is commonly accepted that optimal CD8 + T cell responses require a third signal – usually mediated by an inflammatory cytokine – how CD8 + T cells are regulated during chronic inflammation is less well understood (13).…”
Section: Discussionmentioning
confidence: 99%
“…We have proposed to define the Mtb antigen repertoire expressed in vivo during pulmonary infection. The lung is the primary organ in which Mtb resides and interacts with the human immune system9112122, and where it initiates the process of infection and pathogenesis, setting the stage for future transmission.…”
mentioning
confidence: 99%
“…The required duration of chronic illness has ranged from more than three months to more than twelve months (USDHHS, 2010a; Hwang et al, Anderson, 2017; USDHHS, 2010b) and some researchers have suggested that the medical condition needs to be permanent to qualify (Bernstein et al, 2003;McKenna and Collins, 2010). In the setting of infectious disease in general, the term "chronic" often implies a minimum duration of six months, and with chronic Pseudomonas and Mycobacterial infections the chronically infecting pathogens may be capable of "evading or subverting the immune response" to "establish chronic infection with a time course of years to decades, often resulting in persistent inflammation and disease" (Pressler et al, 2011;Behar et al, 2014). In the case of TBDs, this process often becomes established and persists after 3-6 months of untreated or inadequately treated infection (Cameron et al, 2014;.…”
Section: Length Of Infectionmentioning
confidence: 99%